Desain Nozle Sistem Pengisi Botol Otomatis - Junaidi, Junaidi; Sarjana, Sarjana (JiTEKH, 2022)
Machinery is equipment that is absolutely necessary for companies in carrying out the production process. The bottle filling machine is one of the automatic machines that functions to fill liquid products into packaging. In the development of automation systems, of course, here we need a general control device (Universal) that does not require special power in operation. This research aims to get the time needed to fill 250 and 500 ml bottles, design nozzles for bottle filling and make plc program ledder on bottle filling machine. The system design on the Bottle Filling machine so that it can fill and lock the lid automatically by using a controller in the form of a PLC as a full controller of the system. In making ladder diagrams using the 7 gate logic method (gate logic). In wiring diagrams that contain the arrangement of the series of components used, and are intended to facilitate maintenance and repair of electrical systems, wiring diagrams can also speed up fault finding and shorten maintenance time. The structure of the programming algorithm contains the sequence of work processes on each component contained in the machine.